2013
DOI: 10.1371/journal.pone.0057726
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of Heterologous Prime-Boost Immunisation with Plasmodium falciparum Malaria Candidate Vaccines, ChAd63 ME-TRAP and MVA ME-TRAP, in Healthy Gambian and Kenyan Adults

Abstract: BackgroundHeterologous prime boost immunization with chimpanzee adenovirus 63 (ChAd63) and Modified vaccinia Virus Ankara (MVA) vectored vaccines is a strategy recently shown to be capable of inducing strong cell mediated responses against several antigens from the malaria parasite. ChAd63-MVA expressing the Plasmodium falciparum pre-erythrocytic antigen ME-TRAP (multiple epitope string with thrombospondin-related adhesion protein) is a leading malaria vaccine candidate, capable of inducing sterile protection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 45 publications
5
68
0
Order By: Relevance
“…MVA is a nonreplicating derivative of the uniquely successful smallpox vaccine. Thus, its use in humans is completely safe, as proven by many clinical trials, which have been conducted with it (Kaufmann et al, 2002;Cosma et al, 2003;Cebere et al, 2006;Dorrell et al, 2007;Jaoko et al, 2008;Currier et al, 2010;Wilck et al, 2010;Cavenaugh et al, 2011;Garcia et al, 2011;Goepfert et al, 2011;Sheehy et al, 2012;Verheust et al, 2012;Gilbert, 2013;Ogwang et al, 2013). In addition, MVA is genetically stable, easy to manufacture, and very immunogenic (Cottingham and Carroll, 2013;Gilbert, 2013) because of cross-presentation of dying vaccinia virus-infected cells by dendritic cells to T cells (Iborra et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…MVA is a nonreplicating derivative of the uniquely successful smallpox vaccine. Thus, its use in humans is completely safe, as proven by many clinical trials, which have been conducted with it (Kaufmann et al, 2002;Cosma et al, 2003;Cebere et al, 2006;Dorrell et al, 2007;Jaoko et al, 2008;Currier et al, 2010;Wilck et al, 2010;Cavenaugh et al, 2011;Garcia et al, 2011;Goepfert et al, 2011;Sheehy et al, 2012;Verheust et al, 2012;Gilbert, 2013;Ogwang et al, 2013). In addition, MVA is genetically stable, easy to manufacture, and very immunogenic (Cottingham and Carroll, 2013;Gilbert, 2013) because of cross-presentation of dying vaccinia virus-infected cells by dendritic cells to T cells (Iborra et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, the ChAd63-MVA ME-TRAP alone vaccine was tested in a Phase Ib dose escalation study in healthy Gambian and Kenyan adults (Kimani et al, 2014;Ogwang et al, 2013). The encouraging immunogenicity data of the Phase I/IIa studies in UK malaria-naïve volunteers was again confirmed.…”
Section: Liver-stage Subunit Vaccinesmentioning
confidence: 95%
“…In human trials of ME-TRAP and L3-SEPTL, increased production of CD56 + bright NK cells were detected following vaccination, but were not associated with a delayed time to parasitemia [113]. However, in-cell staining assays did measure increased CD4 + IFN-g-producing cells in vaccinated groups [113,114] that were significantly associated with a delayed time to parasitemia [113]. In human studies, subcutaneous immunization with irradiated sporozoites was suboptimal and failed to elicit broad protection from infection.…”
Section: Humoral Immunity To Sporozoitesmentioning
confidence: 99%